The Influence of Input Frequency and L2 Proficiency on the Representation of Collocations for Chinese EFL Learners - Mengchu Yu; Saisai Xu; Lianrui Yang; Shifa Chen (Behavioral Sciences)
Collocations typically refer to habitual word combinations, which not only occur in texts but also constitute an essential component of the mental lexicon. This study focuses on the mental lexicon of Chinese learners of English as a foreign language (EFL), investigating the representation of collocations and the influence of input frequency and L2 proficiency by employing a phrasal decision task. The findings reveal the following: (1) Collocations elicited faster response times and higher accuracy rates than non-collocations. (2) Higher input frequency improved the accuracy of judgments. High-proficiency Chinese EFL learners exhibit better accuracy and faster response times in collocation judgment tests. Additionally, input frequency and L2 proficiency interactively affected both response time and accuracy rate. These results indicate that L2 learners have a processing advantage for collocations, which function as independent entries in the mental lexicon. Both input frequency and L2 proficiency are crucial factors in collocational representation, with increased input frequency and proficiency shifting the representation from analytic retrieval toward holistic recognition in a continuum pattern.